WALLABY early science – I. The NGC 7162 galaxy group. Issue 3 (29th October 2018) - Reynolds, T N; Westmeier, T; Staveley-Smith, L; Elagali, A; For, B-Q; Kleiner, D; Koribalski, B S; Lee-Waddell, K; Madrid, J P; Popping, A; Rhee, J; Whiting, M; et al.
ABSTRACT: We present Widefield ASKAP L -band Legacy All-sky Blind Survey (WALLABY) early science results from the Australian Square Kilometre Array Pathfinder (ASKAP) observations of the NGC 7162 galaxy group. We use archival HIPASS and Australia Telescope Compact Array (ATCA) observations of this group to validate the new ASKAP data and the data reduction pipeline ASKAP soft . We detect six galaxies in the neutral hydrogen (H i ) 21-cm line, expanding the NGC 7162 group membership from four to seven galaxies. Two of the new detections are also the first H i detections of the dwarf galaxies, AM 2159-434 and GALEXASC J220338.65-431128.7, for which we have measured velocities of cz = 2558 and cz = 2727 km s −1, respectively. We confirm that there is extended H i emission around NGC 7162 possibly due to past interactions in the group as indicated by the 40° offset between the kinematic and morphological major axes for NGC 7162A, and its H i richness. Taking advantage of the increased resolution (factor of ∼1.5) of the ASKAP data over archival ATCA observations, we fit a tilted ring model and use envelope tracing to determine the galaxies' rotation curves. Using these we estimate the dynamical masses and find, as expected, high dark matter fractions of f DM ∼ 0.81−0.95 for all group members. The ASKAP data are publicly available.